Research of Stress Intensity Factor of Fatigue Crack of Spur Gear based on Abaqus - Weichi Pei; Jing Chu; Hongchao Ji; Yaogang Li; Jianwei Dong (Jixie chuandong)
The stress intensity factor is an important parameter to study the fracture problem. The occurrence and development of gear cracks can be measured and controlled， which is of great significance for studying the fatigue damage of cracks and predicting life. In order to study the variation law of three-dimensional crack stress intensity factor of spur gears， a three-dimensional finite element model with initial semi-elliptical cracks is established by Abaqus software. The stress intensity factor of the semi-elliptical crack front is calculated， and the influence of crack size， shape and load variation on the stress intensity factor at the leading edge is analyzed. The results show that the cracks of the roots of the teeth mainly manifested as open cracks during the expansion process. As the load increases， stress intensity factor KI also increases， but its distribution rules remain unchanged. With constant load， KI increases with the increase of crack size. In the establishment of semi-elliptical cracks， as the long axis increases， the KI fluctuations on the crack front gradually become smaller.